Women and the informal economy in urban Africa from the margins to the centre - Kinyanjui, Mary Njeri (London Zed Books, 2014)
In this highly original work, Mary Njeri Kinyanjui explores the trajectory of women's movement from the margins of urbanization into the centers of business activities in Nairobi, Kenya and its accompanying implications for urban planning. While women in much of Africa have struggled to gain urban citizenship and continue to be weighed down by poor education, low incomes and confinement to domestic responsibilities due patriarchic norms, a new form of urban dynamism partly informed by the informal economy is now enabling them to manage poverty, create jobs and link women to the circuits of capital and labour. Relying on social ties, reciprocity, sharing and collaboration, women's informal 'solidarity entrepreneurialism' is taking them away from the margins of business activity and catapulting them into the centre.
Includes bibliographical references (pages 125-133) and index.
Keywords: Women in economic development--Africa.